Pengaruh Karakteristik Individu, Lingkungan Kerja Dan Komitmen Terhadap Kinerja Pegawai Pada Dinas Badan Pengelola Keuangan Dan Aset Daerah (BPKAD) Rantauprapat - Baharuddin Yusuf Irianda Harahap; Nova Jayanti Haraha; Abd. Halim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effect of individual characteristics, work environment and commitment to employee performance at the Regional Financial and Asset Management Agency (BPKAD) Rantauprapat. The research method used in this research is quantitative. In this study, the population was 40 employees of the Regional Financial and Asset Management Agency (BPKAD) Rantauprapat. The research sample used saturated sampling technique by drawing the entire existing population to serve as a research sample with a total of 40 people. The data collection techniques used are observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that Individual Characteristics have a positive and significant effect on Employee Performance at the Regional Financial and Asset Management Agency (BPKAD) Rantauprapat. Work Environment has a positive and significant effect on Employee Performance at the Regional Financial and Asset Management Agency (BPKAD) Rantauprapat. Commitment has a positive and significant effect on Employee Performance at the Regional Financial and Asset Management Agency (BPKAD) Rantauprapat. Individual Characteristics, Work Environment and Commitment simultaneously have a positive and significant effect on Employee Performance at the Regional Financial and Asset Management Agency (BPKAD) Rantauprapat. The coefficient of determination of 0.585 means that employee performance can be explained by the variables of Individual Characteristics (X1), Work Environment (X2) and Commitment (X3) by 58.5%, while the remaining 41.5% can be explained by other variables not examined in this study. Keywords: Individual Characteristics, Work Environment, Commitment, Employee Performance